PROGRAMS OF PARTIES IN SERBIA ON KOSOVO AND METOHIJA ON THE BASIS OF THEIR INTERNET PRESENTATIONS - Miketić, Uroš D. (Politeia, 2020)
This paper, using the operational method of content analysis, gives an overview of the programmatic attitudes of the parties in Serbia about the province of Kosovo and Metohija.  We have used internet presentations of the parties in our case, but in some cases this meant that these were outdated programs from the period of diametrically opposed political circumstances in the country and the world, or general presentations without stating when and where the program was adopted. In any case, the Kosovo and Metohija issue is recognized by most parties, especially those with the most numerous membership and a long tradition, as an issue of first-class state importance. The parties are almost unanimous when it comes to protecting the rights of Serbs, their cultural heritage, and the economic interests of Serbia in the province. However, the positioning of the parties with regard to the final status of the province has brought major differences. Some parties stand firmly on the position of Resolution 1244 and the 2006 Constitution of the Republic of Serbia in relation to this matter, while on the opposite side are those political factors advocating for a permanent solution based on compromise. The statements of contemporary political actors in Serbia about the province of Kosovo and Metohija are not the subject of this paper, but we are exclusively focused on programs as a permanent testimony to the attitude of political circles in Serbia towards the aforementioned issue to this day.
Keywords: Kosmet; status and position of Kosmet; political parties in Serbia; political program